Modular Class-AB Current Multiplier Based on Fully-Differential Hyperbolic Transconductor - Metha Kongpoon (My University, 2021)
This paper presents a new class-AB current multiplier using fully differential hyperbolic sine transconductors based on floating-gate transistors. The proposed multiplier is developed from a hyperbolic sine multiplication identity which inherently provides a class-AB operation. The proposed multiplier was designed using 0.35 μm AMS CMOS process. Simulation results show that the proposed multiplier achieves -30 dB THD for high input modulation index of 23 while utilizing power consumption of 60 nW under a supply voltage of 3 V.
Keywords: Analog and Mixed-Signal Circuit Design; Neural Networks and Reservoir Computing; Quantum-Dot Cellular Automata